STRATEGI PENGEMBANGAN KOMODITAS PORANG DI INDONESIA DARI PERSPEKTIF PRODUSEN DAN KONSUMEN (Forum Penelitian Agro Ekonomi, 2023)
Porang (Amorphophallus muelleri) has become a popular commodity in recent years in Indonesia, especially because of its potential as an alternative food ingredient in addition to various other advantages. This plant is easy to cultivate, including in forest areas, has high export demand, and is believed to be a healthy food source. However, the fluctuating price of porang has reduced farmers' interest in planting it. For this reason, it is important to analyze the dynamics of porang farming at the producer level, as well as consumer preferences for derivative products; so that future development strategies can be obtained. Various references show that porang farming can provide profits of up to 3 to 5 times the production costs, with a range of up to IDR 100–200 million per hectare. Meanwhile, from the consumer side, positive preferences pay attention to health aspects, color, taste, uniformity, cleanliness, aroma, brand, packaging, as well as shelf life and price. From these two perspectives, for future development, partnerships between farmers, the private sector, and the government are needed by utilizing the resources each has. One form of activity needed is increasing literacy and intensive promotion to the general public by prioritizing the added health value of people so that the market becomes more open and developed.
Keywords: cultivation; commodities; added value; porang; farming; budi daya; komoditas; nilai tambah; usaha tani